Implementasi Aplikasi Toy App dan Modul Ajar Berbasis Proyek di SD Negeri 1 Padenganploso Kabupaten Lamongan - Wahyu Kyestiati Sumarno; Ali Shodikin; Nur Imro’atus Solikha; Novandi Kevin Pratama (Abdimas Universal, 2023)
Digital literacy is one of the most needed 21st century skills. The effectiveness of integrating the use of technology in project-based learning has proven to be effective in increasing digital literacy skills. Toy App is an Android-based application designed as a medium for learning basic literacy and numeracy. The purpose of this community service activity is to implement the Toy App application and project-based teaching modules to increase digital literacy in students. This activity was carried out for students at SD Negeri 1 Padenganploso, Pucuk District, Lamongan Regency. The results of this activity show that the implementation of the Toy App and project-based teaching modules has a positive impact on increasing digital literacy in students. In addition, the learning process is also more fun. Based on these results, the application of the Toy App application and project-based teaching modules can be used as an alternative in supporting digital literacy in elementary school students.